2012
DOI: 10.1002/lary.23655
|View full text |Cite
|
Sign up to set email alerts
|

Artificial neural network classification of pharyngeal high‐resolution manometry with impedance data

Abstract: Purpose To use classification algorithms to classify swallows as safe, penetration, or aspiration based on measurements obtained from pharyngeal high-resolution manometry (HRM) with impedance. Study design Case series evaluating new method of data analysis. Method Multilayer perceptron (MLP), an artificial neural network (ANN), was evaluated for its ability to classify swallows as safe, penetration, or aspiration. Data were collected from 25 disordered subjects swallowing 5 or 10 ml boluses. Following extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 27 publications
0
28
1
Order By: Relevance
“…The output of HRM is objective pressure data with high temporal and spatial resolution. HRM has the capability to determine objective changes in swallowing pressure in patients with dysphagia [1820]. HRM data is objective with good temporal and spatial resolution and thus can reveal subtle changes in swallowing-related pressure and timing events in patients in the early stages of PD, before signs or symptoms of overt dysphagia appear.…”
Section: Introductionmentioning
confidence: 99%
“…The output of HRM is objective pressure data with high temporal and spatial resolution. HRM has the capability to determine objective changes in swallowing pressure in patients with dysphagia [1820]. HRM data is objective with good temporal and spatial resolution and thus can reveal subtle changes in swallowing-related pressure and timing events in patients in the early stages of PD, before signs or symptoms of overt dysphagia appear.…”
Section: Introductionmentioning
confidence: 99%
“…Automated analysis holds the promise of standardizing measures, with algorithms that can maximize use of spatiotemporal data in representing swallowing physiology [21, 30, 31]. The value of impedance data in the pharynx may be greater when combined with manometric measures in composite analysis [29, 32]. Ongoing research is needed to provide the evidence base that can define the role of HRM in swallowing care delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, the classification accuracy of 84.2% observed for penetration-aspiration was based on a binary classification scheme (normal versus penetration+aspiration) and was lower than our previously reported value of 89.4% obtained using a ternary scheme (normal versus penetration versus aspiration). 13 This disparity may be due to the absence of impedance measurement, which is useful for detecting bolus residue. 6 Future studies using combined HRM-impedance to identify abnormalities observed on videofluoroscopy may produce even stronger correlations than those observed here.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 We previously applied ANNs to classify HRM data into normal and disordered swallows 12 as well as identify penetration and aspiration. 13 While application to identify clinically significant events currently assessed on videofluoroscopy such as aspiration is an important step in the development of HRM, videofluoroscopy can assess much more than aspiration status.…”
Section: Introductionmentioning
confidence: 99%